207 Cervical cancer in young women treated at a single institution – a retrospective cohort study. (18th September 2019) - Njovu, C; Simonds, H
Abstract : Objectives: The aim of the study was to evaluate demographics and treatment outcome in young women under the age of 40 years with cervical cancer treated at a single institution in South Africa. Methods: Retrospective study of patients younger than 40 years with cervical cancer referred for radiation from January 2015 to December 2018. The MOSAIQ® patient management system was used as the data source of patient names. Data collected included patient demographics; HIV status; stage; treatment and survival outcome. Results: In the time period 96 patients under the age of 40 years were referred for radiotherapy. The median age was 33 years (24–38 years); 15.6% (n=15) were under the age of 30. Overall, 36.5% were HIV-positive. Disease characteristics included 91.7% squamous cell carcinoma on histology; 65.6% (n=63) were Stage IIIB and above. The very young (under 30 years) had a high proportion presenting with advanced stage disease, 73.3% (n=11). Seventy-one patients (74%) received radical CCRT, RT or adjuvant CRT. HIV-negative patients were significantly more likely to be prescribed curative therapy (82% vs 60%; p=0.018). The majority of the cohort, 77 patients (80.2%), received a minimum of 40Gy EBRT. Of the 71 patients who received radical therapy, 17 (23.9%) had a recorded date of death by study end, with no significant difference by HIV-status. Conclusions: The young women presenting with cervical carcinoma at our institution had a high prevalence of HIV and advanced stage. Though HIV status impacted treatment intent, more than 80% of the total cohort received radical radiation or high dose palliation.